2011
DOI: 10.1002/cphc.201100067
|View full text |Cite
|
Sign up to set email alerts
|

p‐Nitrobenzoic Acid Adsorption on Nanostructured Gold Surfaces Investigated by Combined Experimental and Computational Approaches

Abstract: Adsorption of guest molecules on host surfaces can lead to dramatic changes in the spectral properties of the guest. One such effect is surface-enhanced infrared absorption (SEIRA), observed when the guest is adsorbed on, for example, thin films, metal surfaces, or nanotubes. p-Nitrobenzoic acid (p-NBA) exhibits a SEIRA effect when adsorbed on Ag and Au. Herein, the IR spectra of p-NBA adsorbed on a homemade rough Au surface, recorded in reflection mode with an angle of incidence of 16.5°, are reported. This S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…In contrast, a previous FTIR-SEIRAS report indicated that the IR absorption bands for PNBA samples on an Ag island film increased very slowly (or the enhancement factor drops) after the thickness was above ca. 5 nm . This is consistent with the short-range confined electric field and the long-range confined thermal field on nanostructured metal surfaces.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, a previous FTIR-SEIRAS report indicated that the IR absorption bands for PNBA samples on an Ag island film increased very slowly (or the enhancement factor drops) after the thickness was above ca. 5 nm . This is consistent with the short-range confined electric field and the long-range confined thermal field on nanostructured metal surfaces.…”
Section: Resultssupporting
confidence: 84%
“…5 nm. 57 This is consistent with the short-range confined electric field and the long-range confined thermal field on nanostructured metal surfaces. In the presence of the SEIRA effect, ||E loc || 2 in equation 1 is enhanced in comparison to that in the absence of the SEIRA effect and the enhancement factors vary with increasing d. As we have mentioned above, though the electric field enhancement of SEIRA occurs only within a few nanometers from the metal surface, the photothermal effect caused by SEIRA may extend to tens to hundreds of nanometers.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The observed features in the photoluminescence spectra could be explained by the close location of the PC stop-zone and the plasmon resonance region in gold nanoparticles to the region of emission of initial opal and the fluorescence property of gold particles [8]. Thus, it was shown in [9] that gold particles have a plasmon resonance near 530 nm. Meanwhile, the gold particles or gold rough surface show the photoluminescence in the visible region [8].…”
Section: Results Of Experimentsmentioning
confidence: 95%
“…Noort and co-workers suggested a five-parameter, threecompartment model that assumes a triphasic adsorption process in which the slow fraction can divide into two compartments, a slowly adsorbing one and a very slowly adsorbing one. [43][44][45][46] An advantage of this model is that it theoretically describes a continuous distribution of sorptive compartments with only two parameters. Shuler, Miller and Riddle studied a new, two-parameter model to express the kinetics of adsorption based on the statistical gamma function.…”
Section: Adsorption Kinetics Modelmentioning
confidence: 99%